1999
DOI: 10.1080/10473289.1999.10463880
|View full text |Cite
|
Sign up to set email alerts
|

Field Measurements of Particulate Matter Emissions, Carbon Monoxide, and Exhaust Opacity from Heavy-Duty Diesel Vehicles

Abstract: Diesel particulate matter (PM) is a significant contributor to ambient air PM 10 and PM 2.5 particulate levels. In addition, recent literature argues that submicron diesel PM is a pulmonary health hazard. There is difficulty in attributing PM emissions to specific operating modes of a diesel engine, although it is acknowledged that PM production rises dramatically with load and that high PM emissions occur during rapid load increases on turbocharged engines. Snap-acceleration tests generally identify PM associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…The 17 runs were carried out over the period July [23][24][25][26][27]1996. The exact times, environmental conditions, and vehicle characteristics observed for each run are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The 17 runs were carried out over the period July [23][24][25][26][27]1996. The exact times, environmental conditions, and vehicle characteristics observed for each run are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…(7) However, no information on the extent of DOCs usage in the eight DEMS mines was used in developing any of the REC exposures. Clark et al (27) studied the relationship between particulate matter (PM) and CO in diesel engines operated under different loading conditions, and concluded that that there was no universal relationship between CO and PM, but that that the CO/PM relationship appears to be unique for each engine type and perhaps for each engine. Consequently, the assumption of a fixed quantitative relationship between CO and REC is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Schauer et al 102 Clark et al 106 in 1999 reported dynamometer results for two 1996 D buses. Clark et al 107 showed, in 2003, PM emissions from dynamometer measurements for four HDDVs (average model year 1993.5) by proportioning the The error bars represent the 95% confidence interval for the respective decile mean, calculated using a bootstrap technique.…”
Section: Discussion and Comparison With Previous Studiesmentioning
confidence: 99%